Evidence of a 2D Electron Gas in a Single‐Unit‐Cell of Anatase TiO2 (001). Issue 16 (5th April 2022) - Troglia, Alessandro; Bigi, Chiara; Vobornik, Ivana; Fujii, Jun; Knez, Daniel; Ciancio, Regina; Dražić, Goran; Fuchs, Marius; Sante, Domenico Di; Sangiovanni, Giorgio; Rossi, Giorgio; Orgiani, Pasquale; et al.
Abstract: The formation and the evolution of electronic metallic states localized at the surface, commonly termed 2D electron gas (2DEG), represents a peculiar phenomenon occurring at the surface and interface of many transition metal oxides (TMO). Among TMO, titanium dioxide (TiO2 ), particularly in its anatase polymorph, stands as a prototypical system for the development of novel applications related to renewable energy, devices and sensors, where understanding the carrier dynamics is of utmost importance. In this study, angle‐resolved photo‐electron spectroscopy (ARPES) and X‐ray absorption spectroscopy (XAS) are used, supported by density functional theory (DFT), to follow the formation and the evolution of the 2DEG in TiO2 thin films. Unlike other TMO systems, it is revealed that, once the anatase fingerprint is present, the 2DEG in TiO2 is robust and stable down to a single‐unit‐cell, and that the electron filling of the 2DEG increases with thickness and eventually saturates. These results prove that no critical thickness triggers the occurrence of the 2DEG in anatase TiO2 and give insight in formation mechanism of electronic states at the surface of TMO. Abstract : This paper reports the evolution of a 2D electron gas (2DEG) in anatase TiO2 thin films as a function of thickness. The investigation reveals that, once the anatase fingerprint is present, the 2DEG in TiO2 is robust and stable down to a single‐unit‐cell. The results prove that no critical thickness triggers the occurrence of the 2DEG in anatase TiO2 .